We will have the following:
First, we write the both equations: the line and the circle:
![\begin{gathered} y=3x \\ \\ and \\ \\ x^2+y^2=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l4cjie4u7i9qxsc4jvzjwjmwyr8uuds353.png)
This can be seeing as follows:
Now, we determine the point where the line intersects the circle in the first quadrant, so first, we determine the positive part of the circle, that is:
![\begin{gathered} x^2+y^2=4\Rightarrow y^2=-x^2+4 \\ \\ \Rightarrow y=√(-x^2+4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7x214g8cxbp6xt0e29bwr3ddy2x6yq6x9b.png)
Now, we equal this expression and the line:
![\begin{gathered} 3x=√(-x^2+4)\Rightarrow(3x)^2=(√(-x^2+4))^2 \\ \\ \Rightarrow9x^2=-x^2+4\Rightarrow10x^2-4=0 \\ \\ \Rightarrow5x^2=2\Rightarrow x^2=(2)/(5) \\ \\ \Rightarrow x=\pm\sqrt{(2)/(5)} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lupuzwmzpx83o8gyn9l7w62zaz7rwo3ppd.png)
From this, we take the positive value, since it the only one that makes sense under the parameters required, now we find the value of y:
![y=3(\sqrt{(2)/(5)})\Rightarrow y=(3√(10))/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/ofzn2dnqg3gl2fpmtnah4qqtj91c31zr99.png)
So, the solution is at the point:
![(\sqrt{(2)/(5)}\frac{}{},(3√(10))/(5))](https://img.qammunity.org/2023/formulas/mathematics/college/mh9iyay7pqa6hvol4c2qor30iwevav5u0u.png)
This can be seeing as follows: